Media Habits Siswa SD Kalangan Kelas Menengah Muslim Urban di Kabupaten Jember - Dawud, Mochammad (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
The technological revolution in the media industry has had a significant impact on the consumption patterns of both society and individuals. The influence is not only on adults and teenagers but also on children. Media has a great power in shaping children's speech and behavior, formulating self-image, and determining expectations. Media Behavior (or habits of media use) is a fundamental concept formed by relatively fixed elements, namely social structure and media structure. Children need media literacy, a concept applied to media consumption patterns. This research was conducted at Full Day School Al Baitul Amien and SD Al Furqon Jember. This study aims to reveal the media habits of urban middle-class elementary school students. To obtain a picture of the behavior of elementary school children from the urban Muslim middle-class group in consuming media, especially television and smartphones. The results of this study found that elementary school children from the Muslim middle-class in Jember district utilize most of their time for social media, playing online games, and studying. They use social media more for communication and entertainment. Although television is available in their homes, the time spent watching TV at home is still within a tolerable limit, which is only 1 to 2 hours per day. Meanwhile, the duration of time spent using smartphones exceeds the tolerable amount, which is 2-6 hours per day, especially during school holidays. They use their phones for communication and entertainment through social media and online games. The rest of the time, they use their phones for studying purposes.